Photoluminescence Analysis of Injection-Enhanced Annealing of Electron Irradiation-Induced Defects in GaAs Middle Cells for Triple-Junction Solar Cells*Supported by the National Natural Science Foundation of China under Grant Nos 10675023, 11075018 and 11375028, and the Specialized Research Fund for the Doctoral Program of Higher Education under Grant No 20120003110011. (May 2016) - Zheng 郑, Yong 勇; Yi 易, Tian-Cheng 天成; Xiao 肖, Peng-Fei 鹏飞; Tang 唐, Juan 娟; Wang 王, Rong 荣
Abstract : Photoluminescence measurements are carried out to investigate the injection-enhanced annealing behavior of electron radiation-induced defects in a GaAs middle cell for GaInP/GaAs/Ge triple-junction solar cells which are irradiated by 1.8MeV with a fluence of 1 × 10 15 cm −2 . Minority-carrier injection under forward bias is observed to enhance the defect annealing in the GaAs middle cell, and the removal rate of the defect is determined with photoluminescence radiative efficiency recovery. Furthermore, the injection-enhanced defect removal rates obey a simple Arrhenius law. Therefore, the annealing activation energy is acquired and is equal to 0.58 eV. Finally, in comparison of the annealing activation energies, the E5 defect is identified as a primary non-radiative recombination center.